Companion Publication of the 2021 Conference on Computer Supported Cooperative Work and Social Computing 2021
DOI: 10.1145/3462204.3481780
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Interpersonal Space of Online Meetings: An Exploratory Study of “We-ness”

Abstract: The covid-19 pandemic has severely limited the possibility for people to meet physically, which forced many individuals and organizations to employ online meetings as their predominant mode of communication. A potential problem with the unprecedentedly central role of online meetings in a wide range of everyday activities is the disruption it may cause to intersubjective experiences, an intuitive mutual understanding of the participants and their thinking of themselves as a group, a "we". To address this probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Having their practicum teacher play a very direct role in helping during their projects shapes these interactions. Supporting and preparing for interpersonal connectedness, "team experience", and the sense of being "we" in online meetings is central (Kaptelinin et al, 2021).…”
Section: Limitations and Premises For Learning Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Having their practicum teacher play a very direct role in helping during their projects shapes these interactions. Supporting and preparing for interpersonal connectedness, "team experience", and the sense of being "we" in online meetings is central (Kaptelinin et al, 2021).…”
Section: Limitations and Premises For Learning Outcomesmentioning
confidence: 99%
“…In line with our experience with online practicums, they claim that this is not always the case. Kaptelinin et al, (2021) indicated that "the current massive transition from physical to online meetings may mean that complete "team lifecycles", from emergence to dissipation, will increasingly involve little or no physical meetings". This trend is also evident within kindergarten education, as the use of online meetings is becoming a part of normal practice.…”
Section: Unintended But Valuable Learning Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…By traditional definitions of communication richness [28], video or audio conferencing would be considered a rich communication mechanism as it conveys information in many forms (i.e., through body language and tone). Despite this, this virtual mechanism still has its drawbacks: Kaptelinin et al [48] found that online meetings have lower overall experience scores than in-person meetings, and it is harder to coordinate and share ideas.…”
Section: Collaboration Mechanismsmentioning
confidence: 99%
“…As of October 2023, 12% of full-time American employees were working remotely, and 30% were hybrid [5], with these numbers expected to increase [8]. For decades, Human-Computer Interaction (HCI) researchers have studied distributed teams, identifying current challenges [14,48,86], and designing technical solutions to overcome them [64,79,97]. One well-documented challenge in distributed collaboration is a loss of awareness of colleagues' work [4,31].…”
Section: Introductionmentioning
confidence: 99%